Optimization of Chitosan/Pectin Polyelectrolyte Complex Using Glutaraldehyde-Crosslinked as Methylene Blue Absorbent - Silitonga, Friska Septiani; Siswanta, D.; Mudasir, Mudasir; Gurning, K. (Rasayan Journal of Chemistry, 2022)
This study aimed to make a crosslinked chitosan/pectin membrane with glutaraldehyde under conditions of time, pH, and maximum concentration in the adsorption of methylene blue. The first step was to synthesize the chitosan-pectin polyelectrolyte complex membrane which was cross-linked with glutaraldehyde by dissolving pectin in distilled water, then combining chitosan in acetic acid and adding glutaraldehyde and evaporated at 70°C. The second step is to characterize the synthesized membrane using FTIR, and determine the optimum contact time, optimum pH, and maximum concentration of methylene blue in adsorption. The results showed that the optimum mass ratio of 10% glutaraldehyde crosslinked polyelectrolyte membranes of 10% glutaraldehyde at the optimum contact time to adsorb methylene blue was 40 minutes with an adsorption capacity of 7,125 mg/g; The optimum pH is 6; the maximum adsorption concentration of methylene blue was 100 mg/L with the maximum adsorption capacity being 40.244 mg/g and following the Langmuir isotherm, the equilibrium constant (K) was 1.42 × 104 L/mol. Keywords: Chitosan/Pectin, Crosslinked, Glutaraldehyde, Adsorption, Methylene Blue.